Silício e ácido giberélico na produção de gladíolos em ambiente protegido - Zanão, Maristela Pereira Carvalho (2017)
Floriculture is an extremely lucrative activity. The gladiolus is among the most important cut flowers in the country. The application of silicon and gibberellic acid has shown positive results in some cut flowers. The objective of this work was to evaluate the application of silicon and gibberellic acid in the gladiolus cultivated in a pot in a protected environment. In the first experiment the silicon application in drench to the cultivation substrate of three gladiolus cultivars was evaluated. The experimental design was a randomized block design in a 3x4 factorial scheme [three gladiolus cultivars (White Friendship, Rose Friendship and Red Beauty) x four doses of silicon (0, 150, 300 and 600 mg dm-3)], with five replicates. Each experimental unit consisted of a pot with two plants. Phytotechnical characteristics were evaluated in addition to nutrients and silicon foliar contents. In the second experiment were evaluated high concentrations and application methods of gibberellic acid for the production of flower spikes and corms of gladiolus cv. White Friendship. The experimental design was randomized blocks with two application methods of gibberellic acid (GA3): foliar spray and corm soaking. Each application of GA3 was carried out at four concentrations (0, 250, 500, 1000 mg L-1 of GA3), and was replicated six times. The cultivars White Friendship and Red Beauty produced taller plants, with longer, larger and heavier flower stems. The order of nutrient content in the leaves of the three cultivars was the same, with K > N > Ca > Mg > S > P > Fe > Mn > B > Zn > Cu. The gladiolus cultivars were classified as non-accumulating of Si. The application of Si in the gladiolus culture did not influence any evaluated phytotechnical variables and nutrient uptake. High concentrations of GA3 are not recommended for the production of flower spikes and corms of the gladiolus ‘White Friendship’cultivar. Corm soaking anticipated spike harvest and boosted cormel-per-plant yield. Regardless of the application method, 550 mg L-1 of GA3 increased cormel yield.